The Effect Of Quality Of Service And Promotion On Purchase Decision (Consumer Survey at Sandy Make up Tasikmalaya) - Neti Setianingsih; Depy Muhamad Pauzy; Suci Putri Lestari (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect simultaneously and partially of Quality of service, Promotion, Purchase Decision in Sandy Make up Tasikmalaya City. The method used in this research is method a survey. The research data were obtained by distributing questionnaires to 100 respondents. Data analysis in this study used multiple regression analysis using SPSS software. The results of this study indicate that the Quality of service, Promotion simultaneously have a significant effect on Purchase Decision. Quality of service partially significant effect Purchase Decision. promotion has a significant effect on Purchase Decision.